Integrative Curriculum Management Strategy In The Formation of Muslim Character: A Case Study at Al-Hikam Student Islamic Boarding School Malang - Muhammad Yusuf; Murdiono Murdiono; Hadi Nur Taufiq; Saimou Hamissou Malam Mohaman Malam Mohaman (IQRO: Journal of Islamic Education, 2025)
Islamic education today faces global challenges that require graduates to be intellectually competent, morally upright, and spiritually mature. Al-Hikam Student Islamic Boarding School in Malang addresses this by integrating higher education with the traditional pesantren system to nurture holistic Muslim personalities. However, strategic models for managing such integrative curricula are still limited. This study investigates the strategic management of an integrative curriculum for character formation at Al-Hikam, focusing on how planning, implementation, and evaluation processes combine the strengths of universities and pesantren to develop insan kamil—individuals with noble character, intelligence, and religious commitment. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis. Thematic analysis and triangulation were applied to ensure validity and depth. Findings indicate that the curriculum functions through three main domains: dirosah (Islamic learning), kesantrian (character and skill development), and kepengasuhan (spiritual and moral supervision). These domains integrate religious and general sciences within a non-dichotomous, transdisciplinary framework, enhancing students’ discipline in worship, moral conduct, leadership, and independence. The study contributes theoretically to Islamic curriculum management and offers a practical, replicable model for campus-based pesantren, supporting the cultivation of adaptive Muslim character in contemporary contexts.